Reproductive patterns among mothers of males diagnosed with Duchenne or Becker muscular dystrophy123. Issue 1 (13th December 2012) - Nabukera, Sarah K.; Romitti, Paul A.; Caspers, Kristin M.; Street, Natalie; Cunniff, Christopher; Mathews, Katherine D.; Fox, Deborah J.; Puzhankara, Soman; Ciafaloni, Emma; James, Katherine A.; Su, Yin; ,
Abstract Diagnosis of a child with Duchenne or Becker muscular dystrophy (DBMD) may impact future maternal reproductive choice; however, little is known about the reproductive patterns of mothers with a male child diagnosed with DBMD. Using population‐based surveillance data collected by the muscular dystrophy surveillance, tracking, and research network, the proportion of mothers who conceived and delivered a live birth following the diagnosis of DBMD in an affected male child and factors associated with such reproductive choice were identified. To accomplish this, maternal demographic data were linked to birth certificate data to construct the reproductive history for 239 mothers. Univariable and bivariable analyses were conducted to determine the proportion of mothers delivering a live birth and associated factors. By the time of the current study, 96 (40.2%) of the 239 mothers had at least one live birth following delivery of their oldest affected male child; 53 (22.2%) of these mothers had a live birth before and 43 (18.0%) had a live birth after DBMD diagnosis of a male child. Mothers with a live birth after diagnosis were significantly younger at diagnosis of the oldest affected male child (26.2 ± 4.2 years vs. 31.5 ± 5.5 years), and were less likely to be white non‐Hispanic compared to those with no live birth after diagnosis. These results suggest that about one in five mothers deliver a live birth subsequent to DBMD diagnosis in a male child. Maternal age and race/ethnicity were associated with this reproductive choice. © 2012 Wiley Periodicals, Inc.